Effect of plastic drawing at high temperature on structure and properties of carbon fibers - LI Shuang; CUI Di; WANG Yu; XU Lianghua; TONG Yuanjian (Cailiao gongcheng)
To further modify the mechanical properties and improve the electrical and thermal conductivity of polyacrylonitrile-based carbon fibers， the typical high-strength and high-modulus M40J carbon fibers are applied as raw material. The high-temperature drawing characteristics of high-strength and high-modulus carbon fibers and the influence of high-temperature plasticizing drawing on their structure and properties are studied using an online tension meter， XRD， density gradient meter， mechanical testing， and a multimeter. By analyzing the stress response of carbon fibers during high-temperature plasticization and drawing， it is found that when the temperature reaches above 2200 ℃， the stress generated by the fibers during the drawing process remains basically unchanged and the fibers undergoes stable plasticization deformation. This indicates that 2200 ℃ is the transition temperature of plastic deformation for M40J carbon fibers. Plastic drawing at high temperature promotes the growth， elongation， and orientation of graphite microcrystal in the carbon fibers. By applying 6.0% plastic drawing rate to M40J carbon fibers at 2500 ℃， the tensile modulus increases from 368 GPa to 503 GPa， the tensile strength remains good （4.49 GPa）， the electrical resistivity decreases from 11.26 μΩ·m to 9.05 μΩ·m， and the thermal conductivity increases from 63.60 W·m-1·K-1 to 100.73 W·m-1·K-1.